Cadmium carbonate-collagen nanofiber as well as preparation method and application thereof

By orderly growing cadmium carbonate nanoparticles inside collagen fibers to form cadmium carbonate-collagen nanofibers with a directional structure, the problem of insufficient performance of existing inorganic and organic materials memristors is solved, and the effect of high memristor resistance and simplified preparation process is achieved.

CN119753867AActive Publication Date: 2025-04-04WUHAN UNIV OF TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411813715.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-04
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

Existing inorganic material memristors are insensitive to voltage and current changes, while the resistance switching performance of organic material memristors is poor, making it difficult to develop an inorganic-organic composite material-based memristor that integrates the advantages of both.

Method used

By orderly and densely growing cadmium carbonate nanoparticles inside the collagen fibers, a directional structure of cadmium carbonate-collagen nanofibers are formed to serve as a memristor functional layer to improve ion transport efficiency.

Benefits of technology

The cadmium carbonate-collagen nanofibers with high memristor resistance simplify the nanowire transfer step, reduce energy consumption, and have good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753867A_ABST
    Figure CN119753867A_ABST
Patent Text Reader

Abstract

The invention relates to a cadmium carbonate-collagen nanofiber and a preparation method and application thereof.The cadmium carbonate-collagen nanofiber is obtained by orderly and densely growing cadmium carbonate nano-particles in collagen fiber, and the cadmium carbonate nano-particles are arranged in the long axis direction of the collagen fiber in an oriented mode to form an oriented structure. The cadmium carbonate-collagen nanofiber has an ordered directional structure, improves the ion transmission efficiency, has high memristive performance, and has a good application prospect in the field of memristors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nanotechnology for materials and surface science, and specifically relates to a cadmium carbonate-collagen nanofiber and a preparation method and application thereof. Background Art

[0002] Memristors are nonlinear resistors that can store, calculate, and encrypt data due to their unique memristive properties. They are considered to be one of the most promising candidates for the next generation of non-volatile storage devices. Currently, a variety of inorganic and organic materials have been used as memristor materials, but inorganic memristors are insensitive to changes in voltage and current; polymer or metal composite memristors exhibit poor resistance switching performance. The development of inorganic-organic composite memristors that combine the advantages of both is expected to solve this problem. Studies have shown that the structure of the material also has a great influence on the performance of memristor devices. Regular ion channels or ordered structures facilitate ion / atom migration, thereby improving the performance of memristors to a certain extent. Therefore, the development of inorganic-organic composite materials with ordered ion channels is a difficult point in improving the performance of memristors. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a cadmium carbonate-collagen nanofiber and a preparation method and application thereof in view of the deficiencies in the prior art. The cadmium carbonate nanoparticles in the cadmium carbonate-collagen nanofiber are orderly and closely arranged along the long axis direction of the collagen fiber to form a directional structure. The cadmium carbonate nanofiber, as a memristor functional layer, is conducive to rapid ion transmission and has high memristor performance.

[0004] The invention provides a cadmium carbonate-collagen nanofiber. The cadmium carbonate-collagen nanofiber is obtained by orderly and densely growing cadmium carbonate nanoparticles inside collagen fibers. The cadmium carbonate nanoparticles are oriented along the long axis direction of the collagen fibers to form a directional structure.

[0005] According to the above scheme, the particle size of the cadmium carbonate nanoparticles is 20-40 nm, and the diameter of the cadmium carbonate-collagen nanofibers is 200-600 nm.

[0006] The present invention also includes a method for preparing the cadmium carbonate-collagen nanofibers, the specific steps of which are as follows:

[0007] 1) dissolving cadmium chloride and 4-hydroxyethylpiperazineethanesulfonic acid in water to obtain solution A;

[0008] 2) dissolving sodium carbonate and sodium chloride in water to obtain a mixed solution of sodium carbonate and sodium chloride, preparing polyacrylamine hydrochloride to prepare a polyacrylamine hydrochloride aqueous solution, and then adding the obtained polyacrylamine hydrochloride aqueous solution to the mixed solution of sodium carbonate and sodium chloride to obtain solution B;

[0009] 3) Slowly adding the solution A obtained in step 1) to the solution B obtained in step 2) by a peristaltic pump to obtain a mineralization solution, immersing the frozen sectioned tendon slices in the mineralization solution for mineralization, and post-processing to obtain a single cadmium carbonate-collagen nanofiber.

[0010] According to the above scheme, the concentration of cadmium chloride in the solution A in step 1) is 20-60 mM (mmol / L), and the molar ratio of cadmium chloride to 4-hydroxyethylpiperazineethanesulfonic acid is 1-2:1.

[0011] According to the above scheme, the concentration of sodium carbonate in the mixed solution of sodium carbonate and sodium chloride in step 2) is 20-60 mM, and the molar ratio of sodium carbonate to sodium chloride is 1-3:15.

[0012] According to the above scheme, the molecular weight of the polyacrylamine hydrochloride in step 2) is 120000-200000, the concentration of the polyacrylamine hydrochloride aqueous solution is 200-800 μg / mL, and the mass ratio of sodium carbonate in the mixed solution of sodium carbonate and sodium chloride to the mass ratio of polyacrylamine hydrochloride in the polyacrylamine hydrochloride aqueous solution is 150-2000:1.

[0013] According to the above scheme, in step 3), the molar ratio of cadmium chloride in solution A to sodium carbonate in solution B is 1:1-3.

[0014] According to the above scheme, in step 3), the operating speed of the peristaltic pump is 30 rpm.

[0015] According to the above scheme, the mineralization temperature in step 3) is 25-37°C and the mineralization time is 3-24h.

[0016] The present invention also includes the use of the cadmium carbonate-collagen nanofibers in preparing memristors.

[0017] The present invention further provides a memristor prepared by using the cadmium carbonate-collagen nanofibers, wherein the memristor uses the cadmium carbonate-collagen nanofibers as a memristor functional layer.

[0018] The present invention also includes a method for preparing the above-mentioned memristor, which specifically comprises the following steps: two electrodes (such as silver electrodes with silicon dioxide as a substrate) are arranged alternately, and the cadmium carbonate-collagen nanofibers are adhered to a flexible polydimethylsiloxane film with a thickness of 2-5 mm, and the cadmium carbonate-collagen nanofibers are transferred and overlapped on the two electrodes to obtain a memristor. The preparation process can be realized at room temperature and pressure, which simplifies the nanowire transfer steps and reduces energy consumption.

[0019] In the present invention, cadmium carbonate, a functional inorganic material that is easy to form a precursor, is selected to carry out collagen mineralization at 37°C. The confined space inside the collagen fiber causes the mineral particles to grow in an oriented manner inside the collagen fiber, forming a directional structure, accelerating the ion transmission efficiency, and forming a high-performance single nanowire memristor device.

[0020] The beneficial effects of the present invention are: 1. The cadmium carbonate-collagen nanofibers of the present invention have an ordered directional structure, improve the ion transmission efficiency, have high memristive performance, and have good application prospects in the field of memristors; 2. The present invention uses biological matrix collagen fibers as templates to prepare single cadmium carbonate mineralized collagen fibers by collagen intramineralization. The reaction conditions are mild and the preparation process is simple, which is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a SEM image of cadmium carbonate mineralized collagen fibers prepared in Example 1 of the present invention;

[0022] Figure 2 This is the XRD pattern of the cadmium carbonate mineralized collagen fiber prepared in Example 1;

[0023] Figure 3 TEM images of fragments at different mineralization stages cut from a single cadmium carbonate mineralized collagen fiber prepared in Example 1;

[0024] Figure 4 This is an optical photograph of the memristor device prepared in Example 1;

[0025] Figure 5 This is a voltage-current curve diagram of the memristor device prepared in Example 1 when it is first applied;

[0026] Figure 6 is a dual-threshold switching curve diagram of the memristor device prepared in Example 1;

[0027] Figure 7 This is a multiple pulse cycle test diagram of the memristor device prepared in Example 1;

[0028] Figure 8 This is a SEM image of cadmium carbonate-collagen nanofibers prepared in Comparative Example 1;

[0029] Fig. 9 This is the SEM image of the cadmium carbonate-collagen nanofibers prepared in Comparative Example 2;

[0030] Fig.10 This is an optical photograph of the memristor device prepared in Comparative Example 2;

[0031] Fig.11 This is the XRD pattern of the cadmium carbonate-collagen nanofibers prepared in Comparative Example 2;

[0032] Fig.12 This is a current-voltage curve of the memristor device prepared in Comparative Example 2. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below using embodiments in conjunction with the accompanying drawings.

[0034] Example 1

[0035] A cadmium carbonate-collagen nanofiber, the preparation method of which is as follows:

[0036] 1) Dissolve cadmium chloride and 4-hydroxyethylpiperazineethanesulfonic acid in water to obtain 25 mL of solution A, wherein the concentration of cadmium chloride in solution A is 20 mM, and the concentration of 4-hydroxyethylpiperazineethanesulfonic acid is 20 mM;

[0037] 2) Sodium carbonate and sodium chloride were dissolved in water to obtain 25 mL of a mixed solution of sodium carbonate and sodium chloride, wherein the concentration of sodium carbonate in the mixed solution was 20 mM and the concentration of sodium chloride was 300 mM. Polyacrylamine hydrochloride (purchased from Thermo Fisher Scientific, Mw=120000-200000) was prepared into an aqueous solution with a concentration of 800 μg / mL, and 400 μL of the solution was added to the mixed solution of sodium carbonate and sodium chloride to obtain solution B;

[0038] 3) using a peristaltic pump to slowly drop solution A into solution B at a speed of 30 rpm; after the dropwise addition, stirring the resulting mixture on a magnetic stirrer for 10 min to obtain a mineralized solution;

[0039] 4) The turkey leg tendon was frozen (freezing at -25°C for 10 min) and sliced ​​to obtain a 100 μm thick tendon slice, which was immersed in a mineralization solution and then placed in a 37°C oven for mineralization for 9 h. After the mineralization was completed, the slice was taken out, rinsed in deionized water, dried at room temperature, and the fibers were separated on a transfer table with a tungsten needle to obtain a single cadmium carbonate mineralized collagen fiber.

[0040] A memristor was prepared based on the above-mentioned cadmium carbonate mineralized collagen fibers. The specific method was as follows: two silver electrodes based on silicon dioxide were staggered with each other, with an electrode spacing of 2 μm, and a single cadmium carbonate mineralized collagen fiber prepared in this embodiment was adhered using a flexible polydimethylsiloxane film with a thickness of 5 mm, which was transferred and overlapped on the two silver electrodes to obtain a memristor device.

[0041] Figure 1These are the SEM images of the cadmium carbonate mineralized collagen fibers prepared in this example, a is the SEM image of the tendon slice after mineralization, b is the SEM image of a single cadmium carbonate mineralized collagen fiber, and c is the SEM image of the cross-section of a single cadmium carbonate mineralized collagen fiber. It can be seen that the collagen fibers are evenly distributed after mineralization, and it can be clearly observed that a single collagen fiber is fully mineralized with a diameter of about 400 nm. The fracture shows that the interior is filled with cadmium carbonate nanoparticles with a particle size of about 40 nm.

[0042] Figure 2 The XRD pattern of the cadmium carbonate mineralized collagen fibers prepared in this example shows diffraction peaks at angles of 23.5°, 30.3°, 32.9°, etc. corresponding to the standard PDF card (PDF#42-1342) of cadmium carbonate.

[0043] Figure 3 TEM images of fragments at different mineralization stages cut from a single cadmium carbonate mineralized collagen fiber prepared in this example, a on the left is a single collagen fiber fragment in the early stage of mineralization, a on the right is its SAED image, b on the left is the same single collagen fiber in the complete mineralization stage of the fragment, b on the right is its SAED image. By comparison, it can be seen that when the mineralization is incomplete, the diffraction spots are relatively messy, proving that it is a disordered structure; when it is fully mineralized, its diffraction spots prove that its internal crystals grow in a directional manner.

[0044] The optical photograph of a single cadmium carbonate mineralized collagen fiber transferred to the silver electrode during the preparation of the memristor in this example is shown in Figure 4 , a single cadmium carbonate mineralized collagen fiber is overlapped between two silver electrodes.

[0045] Figure 5 This is the voltage-current curve of the memristor device prepared in this embodiment when it is first applied. The memristor device is initially insulated. When the voltage rises to about 3.3V, the resistance suddenly changes, and the memristor device instantly changes from a low-conductivity state to a high-conductivity state. When the applied voltage drops to near zero, the device spontaneously returns to the low-conductivity state. It has a typical "memristor" formation process.

[0046] Figure 6 This is a dual-threshold switching curve of the memristor device prepared in this embodiment. After a typical formation process, only a threshold voltage of 1.5V is required to transform the device into a high-conductivity state. After applying positive and negative voltages to the device, similar hysteresis loops can be formed, indicating the existence of a threshold switching effect.

[0047] Figure 7 This is a multiple pulse cycle test diagram of the memristor device prepared in this embodiment. After multiple stimulation pulses, the memristor operates stably with a consistent current output, and its relaxation time is also very stable during repeated tests, indicating that the memristor device exhibits excellent short-term memristive performance.

[0048] Comparative Example 1

[0049] A cadmium carbonate-collagen nanofiber, the preparation method of which is similar to that of Example 1, except that no polyacrylamine hydrochloride aqueous solution is added to solution B.

[0050] Figure 8 This is the SEM image of the cadmium carbonate-collagen nanofibers prepared in this comparative example. It can be seen from the image that the irregularly shaped large cadmium carbonate crystals are only deposited on the surface of the collagen fiber matrix and cannot enter the interior of the collagen fibers for mineralization.

[0051] Comparative Example 2

[0052] A non-oriented cadmium carbonate-collagen nanofiber, the preparation method of which is as follows:

[0053] 1) dissolving strontium chloride and 4-hydroxyethylpiperazineethanesulfonic acid in water to obtain 25 mL of solution A, wherein the concentration of strontium chloride in solution A is 20 mM and the concentration of 4-hydroxyethylpiperazineethanesulfonic acid is 20 mM;

[0054] 2) Sodium carbonate and sodium chloride were dissolved in water to obtain 25 mL of a mixed solution of sodium carbonate and sodium chloride, wherein the concentration of sodium carbonate in the mixed solution was 20 mM and the concentration of sodium chloride was 300 mM. Polyacrylamine hydrochloride (purchased from Thermo Fisher Scientific, Mw=120000-200000) was prepared into an aqueous solution with a concentration of 800 μg / mL, and 400 μL of the solution was added to the mixed solution of sodium carbonate and sodium chloride to obtain solution B;

[0055] 3) using a peristaltic pump to slowly drop solution A into 25 mL of solution B at a speed of 30 rpm; after the dropwise addition, stirring the resulting mixture on a magnetic stirrer for 10 min to obtain a mineralized solution;

[0056] 4) immersing the frozen sectioned tendon slices (prepared in the same manner as in Example 1) into a mineralization solution, and then placing them in a 37° C. oven for mineralization for 9 hours. After the mineralization is completed, the slices are taken out and rinsed in deionized water to obtain strontium carbonate mineralized tendon slices;

[0057] 5) The strontium carbonate mineralized tendon slice was placed in 20 mL of cadmium chloride solution (concentration 30 mM) and allowed to stand for 30 min, rinsed in deionized water, dried at room temperature, and the fibers were separated on a transfer table using a tungsten needle to obtain single non-oriented cadmium carbonate-collagen nanofibers.

[0058] The non-oriented cadmium carbonate-collagen nanofibers prepared in this comparative example were used as the memristor functional layer, and a memristor device was prepared by the same method as in Example 1.

[0059] Fig. 9From the SEM image of the cadmium carbonate-collagen nanofibers prepared in step 5) of this comparative example, it can be observed that a large number of crystalline particles are mineralized on the outside of a single collagen fiber, and the particles on the surface grow in a randomly oriented manner.

[0060] The optical photograph of a single cadmium carbonate mineralized collagen fiber transferred to the silver electrode during the preparation of the memristor in this comparative example is shown in Fig.10 , a single cadmium carbonate mineralized collagen fiber is overlapped between two silver electrodes.

[0061] Fig.11 The XRD pattern of the non-oriented cadmium carbonate-collagen nanofibers prepared in this comparative example showed diffraction peaks at angles of 23.5°, 30.3°, 32.9°, etc. corresponding to the standard PDF card (PDF#42-1342) of cadmium carbonate, proving that strontium carbonate in the collagen fibers was completely replaced by cadmium carbonate.

[0062] Fig.12 This is a test diagram of the memristor performance of the memristor device prepared in this comparative example. There is no obvious hysteresis loop after five cycle tests on the sample, indicating that the non-oriented cadmium carbonate particles have no memristor performance.

Claims

1. A cadmium carbonate-collagen nanofiber, characterized in that: The cadmium carbonate-collagen nanofibers are obtained by orderly and densely growing cadmium carbonate nanoparticles inside collagen fibers. The cadmium carbonate nanoparticles are oriented along the long axis direction of the collagen fibers to form a directional structure.

2. The cadmium carbonate-collagen nanofiber according to claim 1, characterized in that: The particle size of the cadmium carbonate nanoparticles is 20-40 nm, and the diameter of the cadmium carbonate-collagen nanofibers is 200-600 nm.

3. A method for preparing cadmium carbonate-collagen nanofibers according to claim 1 or 2, characterized in that: The specific steps are as follows: 1) dissolving cadmium chloride and 4-hydroxyethylpiperazineethanesulfonic acid in water to obtain solution A; 2) dissolving sodium carbonate and sodium chloride in water to obtain a mixed solution of sodium carbonate and sodium chloride, preparing polyacrylamine hydrochloride to prepare a polyacrylamine hydrochloride aqueous solution, and then adding the obtained polyacrylamine hydrochloride aqueous solution to the mixed solution of sodium carbonate and sodium chloride to obtain solution B; 3) Slowly adding the solution A obtained in step 1) to the solution B obtained in step 2) by a peristaltic pump to obtain a mineralization solution, immersing the frozen sectioned tendon slices in the mineralization solution for mineralization, and post-processing to obtain a single cadmium carbonate-collagen nanofiber.

4. The method for preparing cadmium carbonate-collagen nanofibers according to claim 3, characterized in that: Step 1) The concentration of cadmium chloride in the solution A is 20-60 mM, and the molar ratio of cadmium chloride to 4-hydroxyethylpiperazineethanesulfonic acid is 1-2:

1.

5. The method for preparing cadmium carbonate-collagen nanofibers according to claim 3, characterized in that: The concentration of sodium carbonate in the solution B of step 2) is 20-60 mM, the molar ratio of sodium carbonate to sodium chloride is 1-3:15, the molecular weight of the polyacrylamine hydrochloride in step 2) is 120000-200000, the concentration of the polyacrylamine hydrochloride aqueous solution is 200-800 μg / mL, and the mass ratio of sodium carbonate in the mixed solution of sodium carbonate and sodium chloride to the mass ratio of polyacrylamine hydrochloride in the polyacrylamine hydrochloride aqueous solution is 150-2000:

1.

6. The method for preparing cadmium carbonate-collagen nanofibers according to claim 3, characterized in that: Step 3) The molar ratio of cadmium chloride in solution A to sodium carbonate in solution B is 1:1-3.

7. The method for preparing cadmium carbonate-collagen nanofibers according to claim 3, characterized in that: Step 3) the peristaltic pump operates at a speed of 30 rpm; Step 3) the mineralization temperature is 25-37° C., and the mineralization time is 3-24 h.

8. Use of the cadmium carbonate-collagen nanofibers as claimed in claim 1 or 2 in the preparation of memristors.

9. A memristor prepared using the cadmium carbonate-collagen nanofibers according to claim 1 or 2, characterized in that: The memristor uses the cadmium carbonate-collagen nanofibers described in claim 1 or 2 as a memristor functional layer.

10. A method for preparing a memristor according to claim 9, characterized in that: The specific steps are as follows: two electrodes are arranged alternately, and the cadmium carbonate-collagen nanofibers described in claim 1 or 2 are adhered using a flexible polydimethylsiloxane film with a thickness of 2-5 mm, which is transferred and overlapped on the two electrodes to obtain a memristor.

Citation Information

Patent Citations

  • Mechanically competent natural polymer based porous grafts for bone repair and regeneration

    CA2752889A1

  • Strontium carbonate collagen composite film as well as preparation method and application thereof

    CN113241402A

  • Mineralized tendon composite material with prestress as well as preparation method and application of mineralized tendon composite material

    CN114732957A

  • Collagen fibril with endofibril highly imitating bone mineralization and preparation method thereof

    CN118477208A

  • Kododenseiserenryukakadomiumunokairyosareta seizohoho

    JP1976069496A